2016
DOI: 10.1007/s12028-016-0260-z
|View full text |Cite
|
Sign up to set email alerts
|

Headache and Its Approach in Today’s NeuroIntensive Care Unit

Abstract: Headache is a very common symptom in the neurointensive care unit (neuroICU). While headache in the neuroICU can be caused by worsening of a pre-existing primary headache disorder, most are secondary to another condition. Additionally, headache can be the presenting symptom of a number of conditions requiring prompt recognition and treatment including subarachnoid hemorrhage, ischemic and hemorrhagic stroke, central nervous system infection, pituitary apoplexy, and cerebral vasoconstriction. The neuroICU also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 95 publications
0
7
0
1
Order By: Relevance
“…Second, our analyses have excluded patients who had a diagnosis of chronic migraine before surgery and therefore it is unclear whether types of anesthesia affect the precipitation of migraine headaches in this population. Third, surgeries that could only be performed with general anesthesia (e.g., brain surgery and ear, nose, and throat surgery) were excluded from analyses, which might decrease the generalizability of study results [ 32 ]. Fourth, a recent study reported that pre-existing migraine was a risk factor for postoperative nausea and vomiting [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, our analyses have excluded patients who had a diagnosis of chronic migraine before surgery and therefore it is unclear whether types of anesthesia affect the precipitation of migraine headaches in this population. Third, surgeries that could only be performed with general anesthesia (e.g., brain surgery and ear, nose, and throat surgery) were excluded from analyses, which might decrease the generalizability of study results [ 32 ]. Fourth, a recent study reported that pre-existing migraine was a risk factor for postoperative nausea and vomiting [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…( Supplementary Table S1 ) Since adverse events after surgery may produce physical and emotional stress and trigger migraine headaches [ 3 , 4 ], we also analyzed the major complications that occurred within 30 days after the index surgery, including pneumonia, septicemia, acute renal failure, pulmonary embolism, deep vein thrombosis, stroke, urinary tract infection, surgical site infection, acute myocardial infarction, cardiac dysrhythmias, and postoperative bleeding. Perioperative uses of blood transfusion [ 29 , 30 , 31 ] and need for intensive care [ 32 ] during the index surgical admission were analyzed. Our analyses also adjusted for the commonly used sympathomimetic drugs prescribed within 180 days after the index surgery, which might affect cerebral blood flow and modify migraine risk, including systemic corticosteroids, ephedrine, and theophylline [ 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…3 Injury-related degranulation of calvarial and periosteal mast cells is likely to cause meningeal inflammation with subsequent activation of trigeminal and trigeminovascular nociceptive fibers. 12 Nerve entrapment or direct lesion with consecutive scar neuroma formation may build the basis for chronic neuropathic pain with allodynia and/or hyperalgesia at the site of incision in cases with chronic headache following craniotomy (e.g., occipital neuralgia due to occipital nerve injury in acoustic neuroma surgery via retrosigmoid approach). 20 21 Further possible contributing factors that have to be mentioned here are postsurgery pneumocephalus and perioperative disturbance of homeostasis because of hormonal-, stress-, sleep-, and nutrition-related alterations as well as caffeine and nicotine withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized our institutional postsurgery standard headache treatment algorithm, which was developed on an interdisciplinary basis with contributions from the departments of neurosurgery and anesthesiology/pain medicine, because to date there are no evidence-based consensus guidelines for the treatment of AHAC. 9 12 The institutional standard regimen for postcraniotomy pain relief is outlined in Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%
“…ливающие препараты опиоидной группы. Кроме того, в литературе не рекомендуют применять нестероидные противовоспа-лительные средства при внутричерепных кровоизлияниях в связи с их влиянием на систему гемостаза и увеличением риска кро-вотечения [2]. Во второй группе из-за необходимости применения большего количества опиоидов случаи чрезмерной седации возникали чаще (-1-2 балла по Ричмондской шкале ажита-ции и седации у 30,2% больных второй груп-пы против 5,2% больных первой группы), что затрудняло своевременную оценку нев-рологического статуса.…”
Section: таблицаunclassified